The Correlation between Pregnant Women with COVID-19 and Mode of Delivery - Taufik Rahman; Fatimah Fatimah; Sundari Mulyaningsih; Dyah Pradnya Paramita; Prasetya Lestari; Amanah Rahma Delia (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: COVID-19 is a virus caused by the Severe Acute Respiratory Coronavirus 2 (SARS-CoV-2). Pregnant women with COVID-19 will likely pose a greater risk compared to nonpregnant women. The Indonesian Society of Obstetrics and Gynecology Association (ISOG) stated that 13.7% of pregnant women are more susceptible to COVID-19. In the maternity management of mothers with COVID-19, the management for the mother and her child should be comprehended.Objectives: This research aims to determine the relationship between the characteristics of pregnant women with COVID-19 with the current mode of delivery at Bagas Waras Hospital, Klaten.Methods: This is quantitative analytical research conducted using a retrospective study approach. The population was maternity mothers with COVID-19 at Bagas Waras Hospital. The sampling method used was non-probability with purposive sampling technique. The statistical test was performed using Spearman’s rho.Results: Most respondents (82%) were in healthy reproductive age, 54.6% were housewives, 80% were in A term gestational age, 63.4% had multigravida, 95.1% had no more than 2 children, and 83.1% underwent sectio caesarea. The analysis showed correlation between maternal age and history of pregnancy (adequate p-value; r = 0.323), between pregnancy history and the number of children (r = 0.259), and between the number of children and the age of the mother (r = 353). Meanwhile, there was no relationship between mothers’ characteristics and the mode of delivery.Conclusion: There was significant relationship between the characteristics of pregnant women with COVID-19 and the current mode of delivery at the Bagas Waras Hospital.